1958
DOI: 10.1002/hlca.660410323
|View full text |Cite
|
Sign up to set email alerts
|

Synthese und Isolierung von Vitamin K2 und isoprenologen Verbindungen

Abstract: 6) Als Vitamin-K,-Reihe bezeichnen wir die Verbindungen der Formel I. 721 (1940). Volumen XLI, Fasciculus 111 (1958) -No. 94. B. S y n t h e s e nDie Synthesen der Verbindungen der Vitamin-K,-Reihe haben wir durch Kondensation von Z-Methyl-l,4-naphtohydrochinon (B) mit Linalool, Neroli-do1 und den hoheren Isoprenologen (A) mit Bortrifluoridatherat als Kondensationsmittel durchgefuhrt. Dabei tritt die Seitenkette unter Allylumlagerung und Wasserabspaltung in 3-Stellung in den Naphtohydrochinonkern ein. Die gebi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1959
1959
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The first representative of the menaquinone family (formerly designated vitamin K2) was isolated by McKee et aL (160) from putrefied fish meal and was thought to be 2-methyl-3-farnesyl-farnesyl-1,4naphthoquinone (15,160). However, it was not until 1958 that the plurality of menaquinones was established, when it was shown that the main compound from fish meal was a menaquinone with seven isoprene units (abbreviated MK-7) and that the related compound MK-6 was present only in minor amounts (109,110). In 1948, Tishler and Sampson (222) found that a soil bacterium named Bacillus brevis contained a menaquinone which, as we now know, had a C35 (farnesylgeranylgeranyl) side chain.…”
Section: General Structuresmentioning
confidence: 99%
“…The first representative of the menaquinone family (formerly designated vitamin K2) was isolated by McKee et aL (160) from putrefied fish meal and was thought to be 2-methyl-3-farnesyl-farnesyl-1,4naphthoquinone (15,160). However, it was not until 1958 that the plurality of menaquinones was established, when it was shown that the main compound from fish meal was a menaquinone with seven isoprene units (abbreviated MK-7) and that the related compound MK-6 was present only in minor amounts (109,110). In 1948, Tishler and Sampson (222) found that a soil bacterium named Bacillus brevis contained a menaquinone which, as we now know, had a C35 (farnesylgeranylgeranyl) side chain.…”
Section: General Structuresmentioning
confidence: 99%
“…As in the case of the ubiquinones, a number of forms of vitamin K occur in microbial cells. They have a common naphthoquinone nucleus and a side chain which varies in the number of isoprenoid units and the degree of saturation and stereochemistry of the side chain (6,32,53,86,143). The basic structure of vitamin K is shown in Fig.…”
Section: Intermediates In Vitamin K Biosynthesismentioning
confidence: 99%
“…Menaquinone-4. MK-4* was prepared from geranyllinalo-ol by essentially the same route as reported by Isler, Riuegg, Chopard-dit-Jean, Winterstein & Wiss (1958). The product was purified by thin-layer chromatography on silica gelwith benzene-light petroleum (1: 1, v/v) as developing solvent.…”
Section: Materials and Methods Materia18mentioning
confidence: 99%